Labour, profitability and gender impacts of adopting row planting in Ethiopia - Vandercasteelen, Joachim; Dereje, Mekdim; Minten, Bart; Taffesse, Alemayehu Seyoum (Oxford University Press, 2018)
Improved technologies are increasingly promoted to farmers in sub-Saharan Africa to address low agricultural productivity. There is, however, a lack of evidence on how adoption affects farmers’ labour use, gender roles and profitability. This paper analyses the farm level impacts of the recently introduced row planting technology in teff production in Ethiopia. Using a randomised controlled trial, we show that row planting significantly increases the total labour requirement and allocation but not teff yields, resulting in a substantial drop in labour productivity. There is no significant profitability effect at the farm level, seemingly explaining the limited success in upscaling the programme.